Factors Affecting Effective Writing in English in Class Four under Northern Trashigang Dzongkhag - Langa Dorji (Progress in Language, Literature and Education Research Vol. 8, 2024)
In recent years, Bhutan has taken significant steps to provide 21st-century competencies in all four strands of the English language. However, the poor performance of the class four written English in exams and their failure to produce good written work in the class due to their poor written skills in English ignited concerns among the educators of Northern Trashigang Dzongkhag, Bhutan. Thus, this study explores the factors affecting effective writing in English in the context of class IV students under northern Trashigang Dzongkhag, employing a sequential mixed methods approach beginning with the survey of the entire class IV students (n=262), of which some students were interviewed (n=20), followed by in-depth interviews and teaching observations of teachers (n= 11), who were selected based on the purposive sampling method. The findings of the study revealed that there are myriads of factors that contribute to poor writing skills in students, and consequently, these factors affect the quality of student writing and the issues that need to be addressed if students’ writing skills are to be improved. This study also unveiled that teachers have the potential to impact students writing skills either positively or negatively.